JAJA BEBANGKIT SEBAGAI PERWUJUDAN PERSEMBAHAN YANG MENGANDUNG NILAI ESTETIK - Budiarta, I Dewa Putu Gede; Buana, Anak Agung Ngurah Gede Surya (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2021)
Hinduism in Bali is a religion that is very full of offerings as gratitude to God in all His manifestations, as well as offerings to the ancestors, also to the Rsi which is translated as a debt, so that all people feel obliged to do the offering. In carrying out the obligation to make offerings with a series of ceremonies, it is always packed with a series that is very symbolic and has a high aesthetic value. Beauty or aesthetics is a very important consideration in carrying out a series of offerings, starting from objects as manifestations of ceremonies, mantra words pronounced in beautiful rhythms, to the attitudes of the performers of offerings with beautiful attitudes and movements in the form of dances. Bebangkit is a series of ceremonies with symbolic meaning which means the manifestation of the great world, contained with symbols of all contents in this universe.